Kalibrasi Wire Feeder Flux Core Arc Welding (FCAW) Mengacu Pada Standar British Standard (BS) 7570:2000 Dan British Standard (BS) European Standard (EN) 50504:2008 - Butar Butar, Hendra; Wijayanti, Ita; Mantik, Andrew; Syukri, Rahmat (JURNAL INTEGRASI, 2024)
In the fabrication industry, the welding process plays a crucial role in both engineering and repair production processes. Continuous use of welding machines can lead to a decline in their effectiveness. Suboptimal machines may produce low-quality products. A common issue encountered is the poor quality of welds, even when each step has been aligned with the Welding Procedure Specification (WPS). One source of this problem is the welding equipment itself. The objective of this study is to calibrate arc welding equipment to ensure it remains within machine standards. Calibration is performed in accordance with BS EN 50504:2008 and BS 7570:2000. The calibration focuses on measuring constant voltage and wire feed speed (WFS). The measurement results for WFS variation indicate that it does not exceed a 10% error margin. This suggests that the WFS complies with the established standards. Consequently, the Lincoln LN-25X wire feeder speed is ready for use in fabrication and production processes.